Tingkat Pemahaman Dan Penerapan Higiene Dan Sanitasi Penjagal Dan Penjual Daging Babi Dan Ayam Di Kota Kupang - Anita Kartini Lakapu; Diana Agustiani Wuri; Annytha Ina Rohi Detha (Jurnal Veteriner Nusantara, 2021)
This study aims to determine the level of understanding and application of hygiene and sanitation of pork and chicken sellers in 5 traditional markets in Kupang City as well as butchers of pork and chickens in Oeba slaughterhouse, Slaughterhouses, Poultry slaughterhouse in Naikoten and home industry in oeba. A total of 100 respondents of pork and chicken sellers and 60 slaughterers of pig and chicken were taken as research samples by questionnaire and interview method. The data collected were analyzed descriptively. The level of understanding of hygiene and sanitation of the pig-slaughterer is 80% good, 10% enough, 10% bad and the application is 60% good, 40% enough while for the understanding of the butchers, the value of 66.7% is good, 23.3% is enough and 10% is bad and the application is obtained value 33.3% good, 66.7% is enough. Among the pig and chicken slaughterers the best level of understanding and application is the butcher of pigs. Levels of understanding of pork sellers on hygiene and sanitation obtained 44% good, 54% enough. 2% bad and the application 32% good, 68% enough while for understanding chicken seller got 48% good, 52% enough with its application 76% good, 24% enough. Chicken meat seller have a better understanding and application of pork sellers. Good understanding affects one's application at work. The results obtained show the level of understanding and application of hygiene and sanitation of pork and chicken sellers and butchers of pigs and chickens in Kupang City.